Guidelines for tourism statistics - United Nations Conference on Trade and Development (New York, United Nations, 1971)
In this guideline, emphasis is placed on statistics covering the number of visitors and visitor-nights, the total of visitors' expenditure and the capacity and rate of occupancy of accommodation establishments.
"United Nations publications. Sales number: E71.II.D.9."
Includes bibliographical references.
osc 29/01/2019
Loans
Keywords: Tourism